Results of potentiometric and optical properties of shabo terroir wines - Иукуридзе, Элдар Жораевич (Eastern-European Journal of Enterprise Technologies, 2015)
The RO-potential value is of particular importance in the production of dry and sparkling wines. Compliance of wine products with regulatory requirements characterizes the quality features and individual characteristics of different bulk wines. These include potentiometric and optical characteristics of bulk wines and wines. The purpose of the work is to conduct research for determining the potentiometric and optical characteristics of bulk wines, provided by the "PTK Shabo" LLC. For determining the optical and potentiometric characteristics, techniques, developed by the National Institute for Vine and Wine "Magarach" were used in the paper. Samples of white table, champagne (Aligoté, Green Sauvignon, Riesling, Traminer Rot, Chardonnay, Telti-Kuruk, Rkatsiteli, White Pinot Noir) and red (Cabernet Sauvignon, Merlot) bulk wines of the "PTK Shabo" LLC were studied, indicators such as oxidation value of phenolic compounds of wine; optical characteristics of bulk wines (color intensity, color hue; yellowness index) were determined. The variation ranges of indicators (RO-potential; oxidation value; yellowness index, yellowness gain), characteristic of bulk wines, produced at the "PTK Shabo" LLC were set. Analysis of the results shows that the indicators correspond to the current regulatory documents of Ukraine.